The global cartooning labour force, its problems and coping mechanisms: the travails of the marginalised cartoonist. (1st October 2010) - John A. Lent
Abstract : Cartoonists, whether print or film, have faced dismal working experiences historically and globally. At times, they have been denied credit for and ownership of their creations, were paid poorly, and laboured under insecure, strenuous, and isolated circumstances. They have also faced the wrath of oppressive governments, political correctness gone awry, and conglomerate takeovers of cartooning/animation industries, with resultant self-censorship, disemployment, and narrowing of job opportunities. This article, drawing on interviews and documentary sources, surveys the state of cartooning in a number of countries around the world. In addition to describing the problems cartoonists face, it finds signs of resistance and solidarity.